Coordination between relay protection functions and excitation system with generator capability curve: Coordination between relay protections and cabability curve - Vučićević, Darko; Buha, Danilo; Marinković, Savo; Gligorov, Saša; Malešević, Nevena (Proceedings, Electrical engineering institute "Nikola Tesla", 2021)
It is common practice for relay protection and excitation system to be adjusted independently, which often for results have uncoordinated operation of some functions. This article presents calculations of some important protection functions. First calculation is about loss of excitation protection, as well as to its coordination with the limit of minimum excitation. Analyzing the coordination settings of this protection with the minimum excitation limiter, we noticed that they are inadequately adjusted so capacitive part of the generator capability curve is not optimally used, for which there is a high need in the transmission system. The second calculation refers to the coordination of the maximum stator current limiter in the excitation system with stator overload protection, overcurrent protection and permitted generator stator overload. It is noted here that this coordination is often not adequately adjusted leading to the following irregularities: - to malfunction of the automatic voltage regulator in certain operating situations which can lead to voltage collapse in the transmission system; - in some operating situations there is no forcing of excitation when it is most needed.